2019
DOI: 10.1038/s41598-018-37381-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Red Nucleus in the Compensation of Parkinsonism may Explain why Primates can develop Stable Parkinson’s Disease

Abstract: Neurological compensatory mechanisms help our brain to adjust to neurodegeneration as in Parkinson’s disease. It is suggested that the compensation of the damaged striato-thalamo-cortical circuit is focused on the intact thalamo-rubro-cerebellar pathway as seen during presymptomatic Parkinson, paradoxical movement and sensorimotor rhythm (SMR). Indeed, the size of the red nucleus, connecting the cerebellum with the cerebral cortex, is larger in Parkinson’s disease patients suggesting an increased activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…This means that in 2019 one can reinforce deep non-dopamine cerebellar and red nucleus circuits that may reduce Parksonism. As demonstrated by Philippens & Vanwersch [100] and Philippens et al, [101] in monkeys and in studies using the scalp surface EEG SMR which is also directly effects the non-dopamine and non-damaged cerebellar compensatory circuits Thompson & Thompson [102].…”
Section: The Future: Cerebellar Z-score Neurofeedbackmentioning
confidence: 86%
See 3 more Smart Citations
“…This means that in 2019 one can reinforce deep non-dopamine cerebellar and red nucleus circuits that may reduce Parksonism. As demonstrated by Philippens & Vanwersch [100] and Philippens et al, [101] in monkeys and in studies using the scalp surface EEG SMR which is also directly effects the non-dopamine and non-damaged cerebellar compensatory circuits Thompson & Thompson [102].…”
Section: The Future: Cerebellar Z-score Neurofeedbackmentioning
confidence: 86%
“…SMR EEG neurofeedback (12-15 Hz) reduced parkinsonism symptoms were attributed to reinforcing the cerebellum circuits that do not involve dopamine and are a separate and compensatory motor system involved with gait and long movements and legs as one walks. Importantly, the studies of Philippens & Vanwersch [100] and Philippens et al, [101] demonstrated a red nucleus change in synaptic number and organization in the EEG SMR group. The red nucleus is a relay nucleus from the cerebellum the thalamus to motor cortex circuits, with minimal dopamine involved.…”
Section: The Future: Cerebellar Z-score Neurofeedbackmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, RN volume was increased in patients with Parkinson's disease and significantly correlated with disease duration and severity, suggesting a compensatory activation of this nucleus (Colpan & Slavin, 2010), probably aimed at compensating the impaired function of the extra‐pyramidal network. Moreover, in nonhuman primates (Philippens, Wubben, Franke, Hofman, & Langermans, 2019) larger RN volume inversely associated with the severity of extra‐pyramidal symptoms. Finally, a damaged striato‐thalamo‐cortical pathway was found to result in a compensatory increase in RN activation (Philippens et al, 2019).…”
Section: Discussionmentioning
confidence: 99%